Typed Lambda Calculi and Applications 10th International Conference, TLCA 2011, Novi Sad, Serbia, June 1-3, 2011. Proceedings - Ong, Luke (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 10th International Conference on Typed Lambda Calculi and Applications, TLCA 2011, held in Novi Sad, Serbia, in June 2011 as part of RDP 2011, the 6th Federated Conference on Rewriting, Deduction, and Programming. The 15 revised full papers presented were carefully reviewed and selected from 44 submissions. The papers provide prevailing research results on all current aspects of typed lambda calculi, ranging from theoretical and methodological issues to applications in various contexts addressing a wide variety of topics such as proof-theory, semantics, implementation, types, and programming.